Pancreatic ductal adenocarcinoma in colonic wall: metastatic disease or cancerized pancreatic ectopic tissue? - Graziana Gallo; Alessandro Mangogna; Gianrocco Manco; Stefania Caramaschi; Tiziana Salviato (Surgical Case Reports, 2020)
Abstract We describe two unusual cases of cancerized ectopic pancreatic parenchyma within the wall of the left colon. Although the morphology of the neoplastic cells and their immunoprofile were consistent with pancreatic ductal adenocarcinoma, the detection of small foci of regular ectopic pancreatic tissue close to dysplastic glands at the periphery of the cancerized mass represented the key diagnostic features. A careful histological examination of surgical samples represents the correct approach to the diagnosis of this rare disease, mostly when total-body CT scan evaluation confirms the lack of bilio-pancreatic masses.